2020
DOI: 10.38035/jafm.v1i1.14
|View full text |Cite
|
Sign up to set email alerts
|

EVENT STUDY OF IPO IN INDONESIA: PUMP-AND-DUMP & FLIPPING STRATEGY ANALYSIS

Abstract: There were three important IPO anomalies: the positive average initial return (improperly called short-term 'underpricing'), the long-term underperformance, and hot/cold IPO. The EVENT STUDY model explained the 'underpricing' based on the assumption that the underwriter sets the initial price equal to the market-perceived true value and investors were rational. IPO prices are affected by demand and supply. The idea of the model was to explore pump-and-dump and flipping patterns exhibited upon IPO anomalies eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
2
3
0
Order By: Relevance
“…To increase the Liquidity Ratio by taking into account the Conditions before the IPO, what must be done by management is the addition of current assets through sales growth or efficiency of operational costs or additional capital from the owner, where the proportion of total current assets can increase compared to total assets. Conditions before the IPO affect the Liquidity Ratio, if the Conditions before the IPO are seen as a positive phenomenon, then this variable can encourage an increase in the Liquidity Ratio Conditions before the IPO had an effect on the Liquidity Ratio, this is in accordance with the results of research: (Munawar & Mahaputra, 2022) and (Sudarmaji, Ambarwati, Keiko Hubbansyah, & Budi Astuti, 2020).…”
Section: Does the Condition Prior To The Ipo Affect The Liquidity Ratio?supporting
confidence: 89%
“…To increase the Liquidity Ratio by taking into account the Conditions before the IPO, what must be done by management is the addition of current assets through sales growth or efficiency of operational costs or additional capital from the owner, where the proportion of total current assets can increase compared to total assets. Conditions before the IPO affect the Liquidity Ratio, if the Conditions before the IPO are seen as a positive phenomenon, then this variable can encourage an increase in the Liquidity Ratio Conditions before the IPO had an effect on the Liquidity Ratio, this is in accordance with the results of research: (Munawar & Mahaputra, 2022) and (Sudarmaji, Ambarwati, Keiko Hubbansyah, & Budi Astuti, 2020).…”
Section: Does the Condition Prior To The Ipo Affect The Liquidity Ratio?supporting
confidence: 89%
“…Effect of Reputation on Employer Branding, this is in line with research conducted by: (Sudarmaji, Ambarwati, Keiko Hubbansyah, & Budi Astuti, 2020), (Parera & Tumanggor, 2021).…”
Section: Effect Of Reputation On Employer Brandingsupporting
confidence: 88%
“…Hence we claimed that under-pricing performed on the Indonesia stock exchange provided that the lowest minimum value existed in the IR variable. At the same time, the highest limit found in the CA30D due to the Buy & Hold practices, Sudarmaji, Ambarwati, Hubbansyah, and Shinta (2020).…”
Section: Resultsmentioning
confidence: 95%
“…Based on empirical studies by Sudarmaji et al (2020) this article revealed that underpricing strategy led to Pump-and-Dump & Flipping strategy occurred on the Indonesia Stock Exchange. The underpricing strategy could be written in the following ways:…”
Section: Resultsmentioning
confidence: 99%